Concrete : microstructure, properties, and materials - Mehta, P. Kumar (Povindar Kumar), 1930-; Monteiro, Paulo J. M. (New York : McGraw-Hill Education, 2014)
"THE MOST COMPREHENSIVE AND CURRENT GUIDE TO THE PROPERTIES, BEHAVIOR, AND TECHNOLOGY OF CONCRETEThis thoroughly updated edition contains new information on: Recently built construction projects worldwide Shrinkage-reducing admixtures Self-consolidating concrete, pervious concrete, internal curing, and other cutting-edge innovations Modeling of ice formation and alkali-aggregate reaction in concrete Environmental impact of concrete Each chapter begins with a preview of the contents and ends with a self-test and a guide for further reading. More than 300 drawings and photographs illustrate the topics discussed in this definitive text on concrete.Comprehensive coverage includes: Microstructure of concrete Strength Dimensional stability Durability Hydraulic cements Aggregates Admixtures Proportioning concrete mixtures Concrete at early age Nondestructive methods Progress in concrete technology Advances in concrete mechanics Global warming and concrete in the future "--
"Comprehensive coverage of the properties, behavior, and technology of concrete--complete with PowerPoint slides and videos--updated to include the latest advances in concrete technology"--
Includes bibliographical references and index.
Keywords: Concrete; Technology & engineering -- Structural